PENERAPAN METODE CERITA UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA SEKOLAH DASAR - Since Lince Betaubun (STKIP Subang, 2023)
An this study aims to improve listening skills in grade II students through the application of the story method. This research is a Classroom Action Research (CAR) conducted in two cycles consisting of four stages, namely, planning, implementation, observation and reflection. The subjects of this study were the second grade students of SD Negeri 2 Merauke, totaling 29 students. The technique of data collection includes observation, listening skills, and documentation. The implementation of the storytelling method in the activities of teachers and students in cycle I was categorized as sufficient, and in cycle II, both teacher and student activities were well-executed. The results of listening skills in cycle I showed concentration indicator at 60%, understanding at 70%, memory at 55%, and conclusion at 45%, with an average score of 65.17. In contrast, in cycle II, the highest improvement in listening skills was found in the understanding indicator at 80%, categorized as excellent, while the conclusion indicator was slightly lower at 65%, with a good qualification and an average score of 75.86. Therefore, the implementation of the storytelling method in Indonesian language learning in elementary school can be considered an effective strategy in enhancing listening skills for second-grade students at SD Negeri 2 Merauke through an engaging, relevant, and experience-centered storytelling method.